Islamic History Of The Meccan Period: A Learning-Oriented Review - Ratnasari, Dwi; Putri, Luqyana Azmiya (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2025)
The life of the Prophet Muhammad SAW in Mecca, before and after being appointed as an Apostle, were the early stage that would determine the Prophet's da’wah journey. With the historical approach, through library research and authoritative literature sources, this paper tries to discuss the history of Islam in Mecca period, a period which is an important foundation for the process of spreading Islam in the world. For 13 years, the Prophet preached in Mecca, inviting people to worship and believe in Allah SWT. Initially, preaching was done secretly and was still limited to the Prophet's family and relatives, until a verse was revealed instructing the Prophet to preach openly. The Prophet and his companions faced various trials and challenges, some of which came from members of his own family. However, the Prophet remained steadfast, and his companions remained firm in their faith, a tangible result of the early period of preaching, which focused on instilling and strengthening aqidah.